2022
DOI: 10.3389/fpsyg.2022.992161
|View full text |Cite
|
Sign up to set email alerts
|

Entrepreneurial mindfulness and organizational resilience of Chinese SMEs during the COVID-19 pandemic: The role of entrepreneurial resilience

Abstract: Organizational resilience is vital to the survival and thriving of enterprises, especially during the COVID-19 pandemic. Although there has been an increasing interest in organizational resilience, the effects from the entrepreneur perspective receive scant attention. Based on upper echelons theory (UET) and personality psychology, we propose a model in which entrepreneurial mindfulness and entrepreneurial resilience could influence organizational resilience of SMEs. We empirically analyzed a sample of 180 ent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 153 publications
0
5
0
Order By: Relevance
“…The relationship between lecturers' dedication to teaching entrepreneurship in HEIs and level of mindfulness is complex (Yener et al, 2018;Liu et al, 2022). Although mindfulness may be beneficial to individuals' personal and professional lives, as has already been demonstrated in its potential for enhancing teachers' skills and performances, especially at low level of education like elementary or secondary school (Hwang et al, 2017), it may not have a substantial impact on their commitment to teaching entrepreneurship due to several reasons (Chavaha et al, 2021;.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between lecturers' dedication to teaching entrepreneurship in HEIs and level of mindfulness is complex (Yener et al, 2018;Liu et al, 2022). Although mindfulness may be beneficial to individuals' personal and professional lives, as has already been demonstrated in its potential for enhancing teachers' skills and performances, especially at low level of education like elementary or secondary school (Hwang et al, 2017), it may not have a substantial impact on their commitment to teaching entrepreneurship due to several reasons (Chavaha et al, 2021;.…”
Section: Discussionmentioning
confidence: 99%
“…Unsurprisingly, literature is emerging on the economic and social impact of COVID-19 on SMEs from financial, innovation and entrepreneurial perspectives (Adam and Alarifi, 2021;Lim et al, 2020;Dai et al, 2021;Liu et al, 2022;Sun et al, 2022). For instance, Robinson and Kengatharan's (2020) investigation of 14 SMEs in Sri Lanka reveals that SMEs struggle with cash flow problems such as paying loans and employees' salaries, experience drops in market demands and, as a result, have had to downsize.…”
Section: The Impact Of Covid-19 On Smesmentioning
confidence: 99%
“…(2021) provide a discussion of the evolving major operational difficulties faced by SMEs. On a related theme, Liu et al. ’s (2022) analysis indicates that relatively entrepreneurially-minded SME owners are more likely to display resilience when dealing with the effects of the pandemic on business operations.…”
Section: The Impact Of Covid-19 On Smesmentioning
confidence: 99%
“…Regarding capabilities, managers with high capabilities can quickly perceive the environment and adequately coordinate the available resources for the firm's long-term development; thus, managerial abilities at the individual level are recognized by most researchers. For example, Liu et al [44] showed that positive entrepreneurial thinking is positively associated with SME resilience. In terms of the organizational aspects of competencies, innovation competencies, change management process competencies, and dynamic competencies have also attracted the attention of researchers.…”
Section: Theoretical Backgrounds 21 High-tech Sme Resiliencementioning
confidence: 99%